FABRIKASI DAN KARAKTERISASI SIFAT OPTIK DARI Ba1-xSrxTiO3 MENGGUNAKAN SPEKTROFOTOMETER ULTRAVIOLET VISIBLE - Yulitah, Detri; Dewi, Rahmi; ', Krisman (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The production of Ba1 -xSrxTiO3(BST) with composition x=0.1 0.2 and 0.3 with the difference temperature of 550, 600 and 650ºC on glass substrat with sol-gel method has been done succesfully. The aim of this research is to obtain the absorbancy and BST substance transmitancy with difference composition and temperature. The characterization was done by using Ultraviolet-Visible spectrophotometer. For composition x=0.1 the maximum absorbancy value on temperature 550, 600 dan 650ºC on each part are respectively 0.105a.u, 0.076a.u and 0.077a.u. For composition x=0.2 the maximum absorbancy value is 0.195a.u, 0.174a.u, and 0.132a.u. For composition x=0.3 the maximum absorbancy value is 0.316a.u, 0.147a.u and 0.108a.u. The maximum transmitancy value for x=0.1 on temperature 550, 600 and 650ºC on each part are respectively 97.9%, 97.7% and 96.6%, for composition x=0.2, each transmitancy value are 90.7%, 98.1% and 94.8%. Meanwhile for composition x=0.3 each transmitancy value is 88.5%, 80.3% and 93.7%. Those results indicate that the difference of temperature influences the absorbancy BST and the more composition of Srontium(Sr) is used, the bigger absorbancy is produced. For transmitancy value, BST is inversely proportional to absorbancy value.